Correlation between Motivation for using Social Media and Self-Regulation in Adolescents - Johan Ramadhan Nurwardan; Elis Yulia Ningsih; Dian Dian; Jatiarta Soewarta (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The rapid growth of social media use among adolescents has raised questions about its psychological impact, particularly in relation to self-regulation. This study aimed to examine the relationship between motivation in social media use and self-regulation behavior in adolescents. Using a quantitative correlational design, data were collected from 204 adolescent respondents through online questionnaires. The instruments used included the Social Media Motivation Scale (Pertegel et al., 2019) and a Self-Regulation Scale based on Zimmerman’s theory of self-regulated learning. Due to the non-normal distribution of one of the variables, Spearman’s Rho correlation analysis was used. The results showed a significant positive correlation (r = 0.456, p < 0.05) between motivation in social media use and self-regulation, indicating that adolescents with stronger and more purposeful motivations for using social media tend to demonstrate higher levels of self-regulatory behavior. These findings suggest that social media, when used with clear intent, can support the development of self-regulation in adolescents. Implications for education, parenting, and further research are discussed.